1) (-∞;2)U(2;+∞)
2)(-∞;-5)U(-5;5)U(5;+∞)
3) (-∞;-6]U[2;+∞)
4) (-7;7)
Объяснение:
1) 2n-4≠0, n≠2, D(f): (-∞;2)U(2;+∞)
2) 25-x²≠0, x≠±5, D(f):(-∞;-5)U(-5;5)U(5;+∞)
3) x²+4x-12≥0
x²+4x-12=(x²+4x+4)-16=(x+2)²-4²=(x+2-4)(x+2+4)=(x-2)(x+6), х=-6;2, а=1>0 - ветки параболы вверх; D(f): (-∞;-6]U[2;+∞)
4) 49-х²>0
(7-х)(7+х)>0
х=±7, а=-1<0 - ветки параболы вниз; D(f): (-7;7)
1) (-∞;2)U(2;+∞)
2)(-∞;-5)U(-5;5)U(5;+∞)
3) (-∞;-6]U[2;+∞)
4) (-7;7)
Объяснение:
1) 2n-4≠0, n≠2, D(f): (-∞;2)U(2;+∞)
2) 25-x²≠0, x≠±5, D(f):(-∞;-5)U(-5;5)U(5;+∞)
3) x²+4x-12≥0
x²+4x-12=(x²+4x+4)-16=(x+2)²-4²=(x+2-4)(x+2+4)=(x-2)(x+6), х=-6;2, а=1>0 - ветки параболы вверх; D(f): (-∞;-6]U[2;+∞)
4) 49-х²>0
(7-х)(7+х)>0
х=±7, а=-1<0 - ветки параболы вниз; D(f): (-7;7)